Integrating a Natural Resource Preservation Dance into SDGs-Based Learning to Foster Elementary Students’ Understanding of Sustainable Living - Hamdani, Fadilah Ahmad; Anasta, Non Dwishiera Cahya (International Conference on Elementary Education, 2025)
The low level of elementary students’ understanding of sustainable living remains a challenge in achieving quality education aligned with the Sustainable Development Goals (SDGs). This study aimsto develop SDGs-based learning media in the form of a dance performance as an educational tool to enhance students’ understanding of sustainable living. This Design and Development (D&D) study,implemented at the Universitas Pendidikan Indonesia, involved three expert validators (a dance expert, an elementary school teacher, and a science literacy expert) and 250 respondents consisting of elementary students, teachers, and pre-service teachers as the subjects of user testing. The developed product is a dance performance themed around natural resource conservation, supported by nature inspired music, and costumes and props created from recycled materials. Validation results show that the media meets the criteria of relevance, clarity, and suitability for learning sustainable living. Audience responses also indicated positive evaluations of the performance’s ability to visualize sustainability principles through movement, rhythm, and expression. These findings demonstrate that integrating dance into SDGs-based learning can serve as an innovative and meaningful approach to strengthening elementary students’ understanding of sustainable living.